Astropedology: palaeosols and the origins of life. (September 2016) - Retallack, Gregory J.
Abstract : Palaeosols are ancient soils formed in sedimentary successions between events of sedimentation, erosion and volcanic activity. Soil formation is regulated by circumstances of climate, vegetation, topographic relief, parent material and time. These factors are quantified by nomopedology, in the form of climofunctions, chronofunctions and other relationships useful for interpreting conditions of the past from palaeosols. In deep time, palaeosols reveal the timing and extent of the Great Oxidation Event of 2.4 Ga. There is also circumstantial evidence for life in palaeosols back to 3.5 Ga on Earth and 3.7 Ga on Mars. These are the oldest known intact profiles, but pieces of palaeosols some 4.56 Ga in age may be represented by carbonaceous chondrite meteorites. Astropedology is the study of very ancient palaeosols and meteorites relevant to the origin of life and different planetary soil systems. Complex chemical assembly, metal catalysis of organic compounds, and the course of hydrolytic reactions as a kind of planetary metabolism make soils an attractive theoretical site for the origin of life. Because dilute solutions tend to an equilibrium that undoes organosynthetic reactions, life is more likely to have arisen on a soil planet like Mars than a water planet like Earth.